Association of Growth Hormone Genes with Performance of Crossbreeds of Sentul Chicken and Arab Chicken Using PCR-RFLP - Sinaga, Josua; Depison, Depison; Gushairiyanto, Gushairiyanto; Harahap, Ratna Sholatia (Faculty of Agriculture, 2025)
This study evaluated the body weight, weight gain, body measurements, and genetic diversity of the Growth Hormone (GH) gene in male and female Sentul-Arab (SeA) crossbred chickens. It also explored the association between the GH gene and these traits. The research involved 30 male and 30 female SeA chickens reared from day-old chicks (DOC) to four months of age. The experimental method used direct observation to collect data, including body weight, weight gain, body measurements, and blood samples. Data were analyzed using t-tests, the Hotellings T test, and Principal Component Analysis (PCA). Molecular analyses assessed genotype and allele frequencies, Hardy-Weinberg equilibrium, heterozygosity levels, and Polymorphic Information Content (PIC). The results indicated that male SeA chickens had significantly higher (P0.05) body weight, weight gain, and body measurements compared to females. GH gene analysis revealed polymorphism, with genotype frequencies of +/+ (0.43), +/- (0.35), and -/- (0.22), consistent with Hardy-Weinberg equilibrium. The heterozygosity levels indicated moderate genetic diversity, while the PIC value fell within the low category. In conclusion, male SeA chickens exhibited superior body weight, weight gain, and body measurements compared to females, with chest circumference and shank length being critical indicators of body size. The polymorphic GH|TaqI gene was associated with body weight, weight gain, and body measurements, with the +/+ genotype showing the most favorable effects.